A comparison of the gender-specificity of age of consent legislation in Europe and China: towards a gender-neutral age of consent in China? - Zhu, Guangxing (European journal on criminal policy and research, 2017)
Age of consent—the age at which young people are considered legally competent to consent to sexual activities—is an important weapon invented by law makers to protect young children from being sexually abused and exploited by predatory adults. In this study, a comparison of the age of consent legislation in 2004 and 2016 in Europe reveals that it is a trend for European law makers to adopt a gender-neutral approach in their age of consent legislation, i.e., the gender of the sexual participants does not affect the legal consequence of the sexual activity and both male and female children, either in heterosexual or homosexual relations, enjoy protection to the same extent. Then the age of consent legislation in China is deeply examined to see whether it is gender-neutral as most of the European jurisdictions. Based on the previous introduction and analysis of Europe and China, this paper concludes that the gender-neutral trend identified in Europe could be instructive for China’s future age of consent legislation.